(untitled) (Research, Society and Development, 2022)
Introduction: The Covid-19 marked history, made the world move towards the fight against this disease, the rampant pandemic due to the ease of transmission of the virus, and its symptoms, however, this disease drew attention due to the emergence of many cases of post-infection people end up showing sequelae of this disease. The most common are parosmia, ageusia, anosmia, which are characterized by alteration or loss of smell and taste. In this sense, it is worth emphasizing the importance of treatments and therapies, aiming to recover the natural state of the senses, since with these anomalies many people began to avoid certain food groups, which are very important for the body. Objective: To relate the changes in smell and taste caused by covid, and the influence on eating behavior. Methodology: This is a literature review with a deductive approach. Results: From the study of literature and articles, it was possible to analyze in general the importance of treatments/therapies aimed at the recovery of the normality of the senses, since they directly influence eating behavior. Discussion of the results: The importance of olfactory therapy was presented, starting from the principle of stimulating our olfactory neurotransmitters that directly help in the dissociation of odors and flavors. Conclusion: The development of the present study allowed us to elucidate how the consequences of this disease are directly related to eating behavior, from the sense-brain/satiety point of view, identifying the main parameters that contribute to associating divergent organs.